2018
DOI: 10.4028/www.scientific.net/ssp.282.101
|View full text |Cite
|
Sign up to set email alerts
|

Selective Wet Etching in Fabricating SiGe and Ge Nanowires for Gate-all-Around MOSFETs

Abstract: A selective wet etching process for fabricating SiGe and Ge nanowires for gate all around transistors is introduced in this paper. Two formulated proprietary chemical mixtures with highly selective etching properties (Si vs. SiGe and SiGe vs. Ge) can effectively dissolve the sacrificial layers with minimal damage to the interstitial nanowire materials. The Auger Electron Spectroscopy (AES) surface characterization indicates that no chemical contamination is left after the wet etching process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Wet alkaline solutions such as NH4OH [208] and TMAH [209,210] have a high selectivity in silicon etching to SiGe, but all have obvious crystal orientation, which is due to the etching rate Si (100) > Si (110) > Si (111). Liu et al reported that ACT R 210 and ACT R 301 reduced the crystal orientation behavior of etching and improved the selectivity ratio of Si (111)/SiGe etch to 13: 1 [211]. In order to overcome the wet crystal orientation anisotropy and liquid capillary effect, dry etching is preferred.…”
Section: High Selective Etching For Channel Full Releasementioning
confidence: 99%
“…Wet alkaline solutions such as NH4OH [208] and TMAH [209,210] have a high selectivity in silicon etching to SiGe, but all have obvious crystal orientation, which is due to the etching rate Si (100) > Si (110) > Si (111). Liu et al reported that ACT R 210 and ACT R 301 reduced the crystal orientation behavior of etching and improved the selectivity ratio of Si (111)/SiGe etch to 13: 1 [211]. In order to overcome the wet crystal orientation anisotropy and liquid capillary effect, dry etching is preferred.…”
Section: High Selective Etching For Channel Full Releasementioning
confidence: 99%
“…By a combination of the Si surface modifier and an effective SiGe corrosion inhibitor in ACT ® SG-201, the selectivity of Si (111)/SiGe 25% is significantly improved as compared to the conventional Si etchants. Consequently, ACT ® SG-201 is more efficient in removing the sacrificial Si layer in the Si/SiGe stack [130]. The reduced Si etch rate anisotropy in combination with an effective SiGe corrosion inhibitor prevents SiGe loss during the NW release [130].…”
Section: Etching Evolutionmentioning
confidence: 99%
“…Consequently, ACT ® SG-201 is more efficient in removing the sacrificial Si layer in the Si/SiGe stack [130]. The reduced Si etch rate anisotropy in combination with an effective SiGe corrosion inhibitor prevents SiGe loss during the NW release [130].…”
Section: Etching Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many studies have proposed Si/SiGe multilayer structures to create an SiGe channel layer [ 17 , 18 , 19 , 20 , 21 ]. In these studies, the solutions of TMAH, mixture solution HF:H 2 O 2 :CH 3 COOH and other alkaline solutions have often been used to obtain a SiGe channel [ 22 , 23 , 24 , 25 ]. However, in the traditional FinFET structure, an important problem is the dry-etching damage to the sidewall caused by plasma sputtering in the fin formation process [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%